Effects of tillage and Npk 15-15-15 fertilizer application on maize performance and soil properties - Arthur, Kyeremateng Francis (2015)
A thesis submitted to the Department of Materials Engineering Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Science in Environmental Resources Management.